Strain selection for growth enhancement of wild and cultivated eucheumatoid seaweed species in Indonesia - Parenrengi, Andi; Dworjanyn, Symon; Syah, Rachman; Pongmasak, Petrus Rani; Fahrur, Mat (Penerbit Universiti Kebangsaan Malaysia, 2020)
A poor seed quality is one of the main constraints to provide a fast growth for seaweed production. It is hoped that seaweed strain selection may lead to production of a high quality seed, resulting in an enhanced growth rate of cultivated seaweeds. The study aimed to obtain a fast growing seaweed strain through proper selection. Three types of base strains were selected: A wild type of Eucheuma denticulatum from Nusa Tenggara Timur (NTT), and two types of cultivated seaweed of Kappaphycus alvarezii from Takalar and Gorontalo, respectively. The collected seaweeds were grown in Laikang Bay using the long line method. The strain selection was based on the daily growth rate (DGR) parameter. The seaweeds were cultivated for 30 days to produce seed, and selected seed material was used for the next cycle for three cycles. The results show that the selected seaweed strains had a higher DGR compared with nonselected (internal control) seed from each of the original forms. DGR of the selected and control seed of the Takalar, Gorontalo, and NTT strains were 6.67% day-1 and 4.91% day-1; 4.23% day-1 and 2.00% day-1; and 2.23% day-1 and 1.20% day-1, respectively. The selection technique increased the DGR up to 1.68% day-1 for three cultivation cycles, while carrageenan content was up to 4.7% higher than the internal control. In conclusion, the best strain for cultivation in Laikang Bay was that of selected from Takalar.